Knowledge and behaviour of nurse/midwives in the prevention of vertical transmission of HIV in Owerri, Imo State, Nigeria: a cross-sectional study (2007)
Background: Mother-to-Child Transmission (MTCT) of HIV remains the main mode of acquisition of HIV in children. Transmission of HIV may occur during pregnancy, delivery or breastfeeding. Studies have shown that some specific interventions help to reduce the transmission of the virus to the baby. In order to target safe, rational and effective intervention to reduce MTCT of HIV, it is necessary to ensure that the nurse/midwife has knowledge of the strategies for the prevention of vertical transmission of HIV. Method: The cross-sectional design was utilized to determine the knowledge and behaviour of nurse/midwives in the prevention of vertical transmission of HIV in Owerri, Imo State, Nigeria. The study sample consisted of 155 nurse/midwives drawn from three selected hospitals through stratified random sampling method. Official permission was obtained from the institutions and consent from participants. Data was collected through the use of a self administered questionnaire. Information sought included respondents' demographic characteristics, knowledge about and behaviour of prevention of vertical transmission as well as factors influencing behaviour. Results: Findings revealed that nurse/midwives had moderate level of knowledge with mean score of 51.4%. The mean score on behaviour was 52.5%, major factors that influence behaviour in these settings were mainly fear of getting infected, irregular supply of resources like gloves, goggles, sharp boxes, and water supply was not regular also. Hypotheses tested revealed that there is a positive relationship between knowledge and behaviour (r = 0.583, p = 0.00). Knowledge level of nurse/ midwives who had educational exposure was not different from those who did not (t = 1.439, p = 0.152). There was a significant difference in the knowledge of nurse/midwives who had experience in managing pregnant women living with HIV/AIDS and those who did not (t = 2.142, p = 0.03). Also, there was a significant relationship between behaviour and availability of resources (r = 0.318, p = 0.000). Conclusion: The study revealed that the nurse/midwives though moderately knowledgeable still had gaps in certain areas. Their behaviours were fairly appropriate. There is need for improved knowledge through structured educational intervention. Resources needed for practice should always be made available and the environment should be much more conducive for practice